Cell fusion as a driver of metastasis: re-evaluating an old hypothesis in the age of cancer heterogeneity - López-Collazo, Eduardo; Hurtado-Navarro, Laura (Frontiers in Immunology, 2025)
Numerous studies have investigated the molecular mechanisms and signalling pathways underlying cancer metastasis, as there is still no effective treatment for this terminal stage of the disease. However, the exact processes that enable primary cancer cells to acquire a metastatic phenotype remain unclear. Increasing attention has been focused on the fusion of cancer cells with myeloid cells, a phenomenon that may result in hybrid cells, so-called Tumour Hybrid Cells (THCs), with enhanced migratory, angiogenic, immune evasion, colonisation, and metastatic properties. This process has been shown to potentially drive tumour progression, drug resistance, and cancer recurrence. In this review, we explore the potential mechanisms that govern cancer cell fusion, the molecular mediators involved, the metastatic characteristics acquired by fusion-derived hybrids, and their clinical significance in human cancer. Additionally, we discuss emerging pharmacological strategies aimed at targeting fusogenic molecules as a means to prevent metastatic dissemination.